O gênero Zornia (Fabaceae - Papilionoideae) no estado da Paraíba, Brasil - Silva, Raquel Pereira Da; Queiroz, Rubens Teixeira De; Fortuna-perez, Ana Paula [UNESP] (Instituto de Pesquisas Jardim Botânico do Rio de Janeiro, 2020)
The genus Zornia with ca. 80 species is composed of two subgenera, Myriadena and Zornia, the last with three sections (Zornia, Isophylla and Anisophylla) and presents a pantropical distribution. Morphologically it is characterized mainly by the flowers arranged in spiciform inflorescences with paired peltade bracteoles, protecting or hiding the calyx of the flower and often the fruit. This research aimed to the species of Zornia in the state Paraíba. Morphological studies were on materials collected and mainly in specimens deposited in the herbaria EAN, JPB, IPA and PEUFR. The species were identified consulting specialized bibliography, complemented by the analysis of digital pictures of the types. For each species was provided description and taxonomic and morphological comments, additionally a key for identification for the genus was also provided. The present seven species were recognized: Zornia brasiliensis, Z. latifolia, Z. leptophylla, Z. guanipensis, Z. myriadena, Z. reticulata, and Z. sericea. The species Zornia guanipensis, Z. myriadena, and Z. sericea are new records for the Paraiba state. The species Z. myriadena, Z. reticulata, Z. brasiliensis e Z. leptophylla have exclusive distribution in the Caatinga. Already Z. guanipensis occurred mainly in the Atlantic Forest specially in the restinga, while Z. sericea e Z. latifolia were distributed in both the Atlantic Forest and the Caatinga.

O gênero Zornia com ca. 80 espécies é constituído de dois subgêneros, Myriadena e Zornia, sendo o último com três seções (Zornia, Isophylla e Anisophylla) e apresenta distribuição pantropical. Morfologicamente é caracterizado principalmente pelas flores dispostas em inflorescências espiciformes com bractéolas peltadas aos pares, encobrindo o cálice, tanto na flor e muitas vezes no fruto. O presente estudo teve como objetivo estudar as espécies de Zornia que ocorrem no estado da Paraíba. Para tanto foram realizados estudos morfológicos com base em materiais coletados e principalmente em coleções depositadas nos herbários EAN, JPB, IPA e PEUFR. A identificação dos materiais foi realizada com o auxílio da bibliografia especializada, complementada pela análise de imagens digitais dos tipos. Para cada uma das espécies foi elaborada uma descrição, comentário taxonômico e morfológico, adicionalmente uma chave de identificação foi feita para todo o gênero. Neste estudo foram registradas sete espécies: Zornia brasiliensis, Z. latifolia, Z. leptophylla, Z. guanipensis, Z. myriadena, Z. reticulata e Z. sericea. As espécies Zornia guanipensis, Z. myriadena, e Z. sericea constituem novos registros de ocorrências para o estado. As espécies Zornia myriadena, Z. reticulata, Z. brasiliensis e Z. leptophylla têm distribuição exclusiva na Caatinga. Já Z. guanipensis ocorre na Mata Atlântica, em restinga, enquanto que Z. sericea e Z. latifolia possuem distribuição em ambos os domínios fitogeográficos.
The genus Zornia (Fabaceae - Papilionoideae) in Paraíba state, Brazil
Keywords: Leguminosae; Dalbergieae; plant taxonomy; floristic diversity; Leguminosae; Dalbergieae; taxonomia vegetal; diversidade florística